Metafora w kulturze popularnej. Przypadek graffiti - Kraska, Mariusz (Wydawnictwo Naukowe UAM, 2007)
The author acknowledges graffiti as a medium creating its own situation of communication. Referring to Scott Lash conception of regime of signification, he underlines that graffiti is critical and destructive to official cultural discourse. This is a kind of anarchistic revolt which is shown within graffiti by a metaphor. It means, unlike to other writings of culture, invalidation of a cognitive function to pragmatic one. One can prove that graffiti metaphor, as a kind of activity, is mainly used in language and through it. In the field of poetics it is presented by destruction of generał language forms, irony and humor, quotation and spelling variations as well as vulgarisms and purnonsens.
Metaphor in popular culture. The case of graffiti